The Validity of the Quaternary Deposits as a Filling Materials in Embankment Dames in Al-Shirqat City / Northern Iraq - Loai Moussa Rawee (Tikrit Journal of Pure Science, 2022)
The research aims to show the validity of the quaternary sediments in the north of Al-Shirqat district as filling materials for dams. Samples were collected from (4) stations representing these sediments in the region. Geotechnical examinations showed that the sediments of this region are clay of low plasticity (CL) and alluvial (ML) having the values ​​of specific weight ranged between (2.65-2.71). Chemical analyzes showed that the gypsum ranges between (1.35-8.08) %, and the percentage of total soluble salts ranged between (3.61-11.52) %, while the pH values ​​were between (8.00-8.11). When comparing the results of geotechnical tests with the physical and chemical specifications of the filling soils according to the specifications of materials and construction works for the National Center for Construction Laboratories and Research, 2003, it shows that all the geotechnical properties of the second station were identical, as well as matching the volumetric gradient, liquidity limit and plasticity factor of stations (4,3,1), except for ratios of total dissolved salts and gypsum content which were out of the limits of the specifications for stations (4,3,1).